The influence of industry sponsorship and conflict of interest on results and conclusions of systematic reviews regarding treatment of knee osteoarthritis - Benjamin Heigle (Osteoarthritis and Cartilage Open, 2021)
Objective: To assess the influence of industry sponsorship and authors’ conflicts of interest on the favorability of results and conclusions of systematic reviews regarding osteoarthritis of the knee. Design: We searched MEDLINE, Embase, and the Cochrane Database of Systematic Reviews on June 26, 2020 for systematic reviews with or without meta-analyses focusing on treatment of osteoarthritis of the knee. Author COI were collected from the systematic review’s COI disclosure statement, the CMS Open Payments Database, Dollars for Profs, Google Patents, the United States Patent and Trademark Office (USPTO), as well as previously published COI disclosure statements. Study sponsorship was determined using information provided in each systematic review’s funding statement. Results: Our study included 53 systematic reviews conducted by a total of 279 authors. Thirty-one authors (of 279; 11.1%) had one or more COI. Fourteen systematic reviews (of 53; 26.4%) had one or more conflicted authors. Of these reviews, only two (of 14; 14.3%) reported narrative results favoring the treatment group, whereas five (of 14; 35.7%) reported conclusions favoring the treatment group. Our results showed no statistically significant association between the presence of COI and the favorability of results (P= 0.11) and conclusions (P= 0.73). Because our sample only included one industry-sponsored systematic review, we were unable to adequately assess for a relationship between industry-sponsorship and favorability of results and conclusions. Conclusion: We found no association between the favorability of systematic review results and conclusions with either the presence of author’s conflicts of interest or industry-sponsorship.